2021
DOI: 10.52088/ijesty.v1i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Efforts to Control Infection Odontoglossum ringspot virus (ORSV) on Orchid

Abstract: Odontoglossum ringspot virus (ORSV) is a orchid virus which infection most widely reported and has spread widely in the world, including in Indonesia. Viral infections can degrade the quality of the orchid plant so it is economically detrimental. To study a disease infection, identification is carried out first to determine the most appropriate method of control. These identification techniques include variations in infection symptoms, host range testing, testing of viral titers, observation of particle morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Biodegradability of this composite will be discuss somewhere else. This is in accordance with research conducted by Ningsing et all, 2012, added banana starch into the matrix polypropylene (PP) and get the value of the tensile strength of the optimum on the addition of the starch 2 grams, but on the addition of starch 3 grams the value of the tensile strength decreased [12]. Other study had also been carried out by Sudi, 2013, mechanical properties on composite matrix polystyrene material added with durian seed starch and obtain tensile strength values decreased on the addition of starch is above 5% [9].…”
Section: Tensile Strengthsupporting
confidence: 90%
“…Biodegradability of this composite will be discuss somewhere else. This is in accordance with research conducted by Ningsing et all, 2012, added banana starch into the matrix polypropylene (PP) and get the value of the tensile strength of the optimum on the addition of the starch 2 grams, but on the addition of starch 3 grams the value of the tensile strength decreased [12]. Other study had also been carried out by Sudi, 2013, mechanical properties on composite matrix polystyrene material added with durian seed starch and obtain tensile strength values decreased on the addition of starch is above 5% [9].…”
Section: Tensile Strengthsupporting
confidence: 90%
“…One of them is the Odontoglossum ringspot virus (ORSV) which is the type of virus that is reported to infect the most and has the widest spread in the world. A previous study (Mahfut, 2021) showed that several natural orchids show variations in symptoms of ORSV induction, namely mosaic, streak, chlorotic, necrotic, and wilting leaf.…”
Section: Introductionmentioning
confidence: 97%
“…The spread of ORSV infection is known to be able to inhibit plant growth and resistance and reduce its aesthetic value periodically (Koh et al, 2014in (Mahfut, 2021). Currently, efforts to control the disease are still using pesticides which cause pollution and environmental damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, use alcohol continuously can cause dryness and irritation by eroding the surface of the skin, dissolving the layer of fat and sebum of the skin. In addition, alcohol also has flammable properties [10] [11]. Therefore, innovation of natural ingredients for hand sanitizer that is safer to the skin is required.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mangrove Avicennia is a source of alcohol, amino acids, carbohydrates, fatty acids, hydrocarbons, minerals, phytoalexin, carboxylic acids, vitamins and glucoside [13]. Besides mangroves, Aceh is rich in patchouli plants, Pogostemin cablin Bench, which contains patchouli alcohol from patchouli oil [14] [11]. Patchouli alcohol is used as a fixative (binding agent) in the perfume industry and a component of cosmetic products.…”
Section: Introductionmentioning
confidence: 99%